Healthcare access barriers for individuals with autism: The awareness of medical professional - Troshanska, Jasmina; Ramadani Rasimi, Teuta; Chichevska Jovanova, Natasha; Rashikj Canevska, Olivera (Edukcisko-rehabilitaciski fakultet u Zagrebu, 2024)
Introduction: Autism spectrum disorder (ASD, autism) is a complex, life-long disorder characterised by two core symptoms, which range in severity: persistent deficits in social communication and social interaction, and restricted and repetitive patterns of behaviour. These behaviours are mainly unfamiliar to healthcare workers, hence the access to healthcare services for individuals with autism becomes challenging. This presentation aims to discuss results regarding the knowledge of autism among medical workers based on their experience and to highlight its importance as a possible barrier to accessing healthcare services. Methodology: To examine the knowledge of autism, a survey was conducted involving 70 medical personnel. In addition, to gather more detailed information about specific experiences of the medical personnel, an interview was conducted with 6 medical doctors. Results: All respondents said that they faced difficulties when working with children with autism - 43% had a problem communicating during the medical examination, while 41% found it difficult to administer medical therapy. In hospitals, individuals with autism are usually referred to one of the medical personnels in the department who is highly skilled in providing services. According to the information from the interviews, this highly skilled person usually has constant close contact with a person or child with autism in their family or friends circle. Conclusion: Medical personnel agreed that they need additional education, informative material, materials for visual communication, and more time to perform a medical examination of patients with autism. Also, they stated that there was a lack of support for families and provision of resources in order for them to prepare children with autism before a doctor’s visit.
Keywords: autism, healthcare, medical personnel